Central functions of corporate controlling systems within CSR terms - Zirkler, Bernd; Brauweiler, Christian; Alickovic, Vedran (Research Papers of Wrocław University of Economics, 2018)
The paper presents three controlling instruments related to CSR and discusses the implementation of those instruments into CSR. The first section deals with the activitybased costing and process-oriented controlling. It shows the differences between these two approaches and stresses their contribution to identification of the non-value creating activities and waste reduction. The second section elaborates on the requirements of modern product costing systems giving a more detailed view about product life cycle costing in the CSR context. The third section focus on target costing where target costs are determined by different market approaches and thus being much more flexible to customer needs and expectations. Finally, the paper introduces a concept of green controlling as a part of CSR
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 209-228
Keywords: activity-based costing; CSR; life-cycle costing; process-oriented controlling; target costing; rachunek kosztów działań; rachunek cyklu życia produktu; controllingzorientowany procesowo; rachunek kosztów docelowych